Use of stable water isotopes to identify stages of the pingo ice core formation - Ju. N. Chizhova; Yu. K. Vasil’chuk (Лëд и снег, 2018)
Te isotopic characteristics of the pingo ice cores are considered. Te distribution of δ18O and δ2H values, dexc, δ18O–δ2H and δ2H–d exc relationships, and the simulation of the distribution of δ18O and δ2H values during the ice formation in a closed system, allowed drawing conclusion about the hydrological conditions and stages of the ice core growth. All pingos (Pestsovoye, Weather, Pingo-20) were formed in draining lake basins in the course of freezing of closed taliks. It is established that the water, which served as a source for the formation of the ice core, was subjected to evaporation still before the ice formation. According to our estimates, the water from which the ice of the Pestsovoye pingo was formed was heavier in values of δ18O and δ2H by 3.9 and 29.7‰, respectively, than the current average annual precipitation in the region. Similarly, for the ice of the core of the Pingo Weather it is 2.9 and 14.5‰, and 5.1 and 27.7‰ for the Pingo-20, respectively. In the ice cores of all considered pingos there is an ice formed in a closed system: in Pingo-20 it is a pure injection ice, while in the Pestsovoye and the Weser ones – the injected-segregated ice. Te frost mounds Pestsovoe and Weser grew under changing hydrological conditions: one part of the ice was formed when there was a free ﬂow of water to the freezing front (open system); the other one – when the water-saturated lenses of the closed talik were frozen (closed system). Te isotopic composition of ice being formed under conditions of a closed system reﬂects isotopic depletion during freezing and ice formation according to the Rayleigh model. It is expressed in a successive decrease in the values of δ18O and δ2H from the frst portions of ice to the last ones as the freezing continued. Te contrast values of δ18O and δ2H in diﬀerent parts of the ice being formed in the closed system may be used as an additional tool to identify direction of freezing. In a closed system, the last portions of ice have the greater contrast of the isotope values as compared to the frst portions.